2019
DOI: 10.1097/prs.0000000000006118
|View full text |Cite
|
Sign up to set email alerts
|

Economics of Lymphovenous Bypass

Abstract: Background: The objective of this study was to compare the economic impact of complete decongestive therapy and lymphovenous bypass in the management of upper extremity lymphedema. Methods: Economics were modeled for a patient with breast cancer–related lymphedema undergoing three different clinical pathways: (1) complete decongestive therapy alone; (2) lymphovenous bypass no longer requiring ongoing complete decongestive therapy; or (3) lymphovenous by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 20 publications
0
10
0
1
Order By: Relevance
“…Economics of lymphatic microsurgery in breast cancer-related LYM were examined in a specific paper [148]. Notwithstanding a few possible criticisms concerning the authors' calculations of conservative treatment (probably overestimated) costs, overall microsurgery proved cost-effective when it was followed by discontinuation of ongoing conservative therapy, which is unlikely to occur in the vast majority of these patients who are affected by a life-long disease.…”
Section: Lymphedemamentioning
confidence: 99%
“…Economics of lymphatic microsurgery in breast cancer-related LYM were examined in a specific paper [148]. Notwithstanding a few possible criticisms concerning the authors' calculations of conservative treatment (probably overestimated) costs, overall microsurgery proved cost-effective when it was followed by discontinuation of ongoing conservative therapy, which is unlikely to occur in the vast majority of these patients who are affected by a life-long disease.…”
Section: Lymphedemamentioning
confidence: 99%
“…One Canadian study quantified the upfront costs of LVA and found that the total upfront cost of LVA is offset by the possible discontinuation of postoperative decompressive therapy. 46 In our results, AlJindan et al 15 reported that all patients were able to discontinue decompressive therapy postoperatively, whereas Ayestaray et al 23 found this was only true in 30% of patients. Similarly, one study found that ILR results in a greater than 40% cost saving in patients undergoing mastectomy with ALND, 47 as the lifetime cost of lymphedema treatment surpass the upfront cost of ILR.…”
Section: Discussionmentioning
confidence: 43%
“…This article also raises a potential economic benefit, through decreased healthcare costs, and improved productivity, and increase in QOL which could be interesting to elucidate further in future studies. 47 The limitations of this study include firstly that this is a report on a singular patient outcome, with no comparative arm. Another important limitation pertains to the method of LVA patency confirmation.…”
Section: Discussionmentioning
confidence: 97%